The importance of cross-border strategies based on the example of the analysis of the Development Strategy of the Euroregion "Beskidy" for 2016-2023 and the Strategy of the Euroregion "Beskidy" for the period 2021-2027 with a vision until 2030 - Sabina Sanetra-Półgrabi (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
The article presents two strategies for the development of cross-border cooperation in the Euroregion "Beskidy", in particular it shows what the Euroregion is in general, then briefly refers to other forms of cooperation, and then characterizes both documents in more detail. Initially, it was defined what the strategy is, what role it plays in the case of cross-border cooperation structures, and the mission of cooperation within the Euroregion "Beskidy", as well as key projects aimed at the development of tourism, culture, sports and education.